Modified positive electrode material and preparation method thereof

By doping metal oxides into the positive electrode material of lithium-ion batteries and using solid electrolytes, weak organic acids and additives during the pickling and coating process, the problem of excessive or low residual alkali on the surface of the positive electrode material is solved, significantly improving the battery electrical and safety performance.

CN119447246APending Publication Date: 2025-02-14BEIJING WELION NEW ENERGY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411580638.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The residual alkali on the surface of the positive electrode material of existing lithium-ion batteries is too high or too low, resulting in poor safety and electrochemical performance of the battery.

Method used

By doping metal oxides in the positive electrode material and using solid electrolytes, weak organic acids and additives to work together during the pickling and coating process, the structure of the positive electrode material surface is stabilized, the total alkali content on the surface is reduced, and the lithium ion migration rate is improved.

Benefits of technology

The electrical and safety performance of lithium-ion batteries is significantly improved, including first-week efficiency, discharge capacity, rate performance and cycle performance, while simplifying the process flow and improving production efficiency and quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005125114500000181
    Figure BDA0005125114500000181
  • Figure BDA0005125114500000191
    Figure BDA0005125114500000191
  • Figure BDA0005125114500000201
    Figure BDA0005125114500000201
Patent Text Reader

Abstract

The invention relates to the technical field of lithium battery positive electrode materials, and discloses a modified positive electrode material and a preparation method thereof. The preparation method comprises the following steps: 1, mixing a positive electrode material and a dopant, and calcining to obtain a doped positive electrode material; m is greater than or equal to 1 and less than or equal to 2, and n is greater than or equal to 1 and less than or equal to 5; e is selected from one or more of Zr, Y, Mg, Ti, Ca, Ce, La, Al, Nb, Ta, W, Mo, Sn, Sb and Sr; 2, adding a solid electrolyte, an organic weak acid, an additive and the doped positive electrode material into a solvent to obtain mixed slurry, and performing acid pickling coating on the doped positive electrode material in the mixed slurry to obtain an acid pickling coating material; the additive is borate and / or phosphate; and 3, roasting the acid-washed coating material to obtain the modified positive electrode material. According to the method provided by the invention, the lithium ion migration rate of the modified positive electrode material can be improved, the total alkali content on the surface is reduced, and the rate capability, the cycle performance and the safety performance of the battery can be further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion battery positive electrode materials, and in particular to a modified positive electrode material and a preparation method thereof. Background Art

[0002] Lithium-ion batteries, with their advantages of high energy density, high voltage and long life, have occupied a major market share in electric vehicles, energy storage systems and mobile electronic devices in recent years. As the key factor affecting the performance of lithium-ion batteries, the research and development of cathode materials is particularly important.

[0003] One of the common problems of positive electrode materials is that their surface is unstable and easily reacts with moisture or air, forming residual surface alkali on the surface. The surface residual alkali reacts with the electrolyte to produce gas during the battery cycle, which can cause safety problems such as battery expansion and pose potential risks of fire and explosion. In addition, these surface residual alkalis are also the key factors that lead to accelerated capacity decay and aggravate structural phase changes. They not only increase the pH of the material surface, aggravate interfacial side reactions, and produce serious gas, thereby affecting its cycle performance and safety performance, but also have an adverse effect on the processing and storage of the material.

[0004] At present, water washing is generally used to remove residual surface alkali. Among them, the cheap and efficient water washing process has been recognized by battery companies and has been widely used in practice. The positive electrode material after water washing can effectively reduce gas generation under high temperature storage, thereby reducing safety issues caused by battery expansion. However, water washing is not effective in removing residual surface alkali.

[0005] Compared with water washing, acid washing is more effective in removing residual alkali on the surface of positive electrode materials. However, the control process of the acid washing process is too harsh, which can easily cause over-washing of the surface of the positive electrode material, resulting in too low residual alkali content on the surface of the positive electrode material, and the surface structure is easily destroyed, which seriously limits and hinders its further application.

[0006] In addition, both water washing and acid washing may reduce the electrochemical performance of the positive electrode material, especially the rate performance and cycle performance of the battery. Therefore, the subsequent coating process is usually combined to improve the electrochemical performance of the positive electrode material. However, coating with inert substances will reduce the initial capacity of the material and affect the overall performance of the battery.

[0007] CN111682190A discloses a method for one-step low-temperature water washing and coating of modified high-nickel ternary positive electrode materials. This method selects nano metal oxides, fluorides, phosphates and solid electrolytes as coating materials, combines low-temperature water washing technology with coating, and realizes the step of obtaining modified high-nickel ternary positive electrode materials. This method simplifies the process and is suitable for large-scale production. However, this method does not solve the problem of residual alkali on the intrinsic surface of oxide solid electrolytes, which will affect the lithium ion diffusion coefficient, and the safety performance and electrochemical performance of lithium ion batteries still need to be further improved.

[0008] Therefore, there is an urgent need to provide a modified positive electrode material and a preparation method thereof that can reduce the residual alkali content on the surface and significantly improve the safety performance and electrochemical performance of lithium-ion batteries. Summary of the invention

[0009] The purpose of the present invention is to solve the problem of poor safety and electrochemical performance of lithium-ion batteries caused by excessively high or low residual alkali on the surface of the positive electrode material in the prior art, and to provide a modified positive electrode material and a preparation method thereof.

[0010] Among them, in the present invention, the inventors have found through research that the metal oxide doped in the positive electrode material can stabilize the structure of the positive electrode material surface during the pickling and coating process, inhibit the H2-H3 phase transition, reduce the serious lattice shrinkage and related microcracks on the surface, and inhibit the chemically unstable Ni 4+ However, some inert metal oxides will remain at the interface of the positive electrode material during the doping process, resulting in a decrease in the migration rate of lithium ions. The interaction between organic weak acids, additives and solid electrolytes can solve the problem of residual inert metal oxides at the interface of the positive electrode material, further improve the migration rate of lithium ions in the positive electrode material, and thus significantly improve the electrical properties of the battery, such as first-week efficiency, discharge capacity, rate performance and cycle performance.

[0011] In the present invention, the dopant, solid electrolyte, organic weak acid and additive work synergistically, which can not only reduce the total alkali content on the surface of the positive electrode material and improve the cycle performance of the battery, but also solve the gas generation problem of the positive electrode material during the cycle, help to form a more stable CEI film, alleviate the surface particle pulverization phenomenon of the positive electrode material, and improve the surface structure stability of the modified positive electrode material, thereby improving the safety performance of the battery.

[0012] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a modified positive electrode material, wherein the method comprises the following steps:

[0013] (1) mixing a positive electrode material and a dopant and calcining the mixture to obtain a doped positive electrode material; wherein the dopant is E m On , 1≤m≤2, 1≤n≤5; E is selected from one or more of Zr, Y, Mg, Ti, Ca, Ce, La, Al, Nb, Ta, W, Mo, Sn, Sb, Sr;

[0014] (2) adding a solid electrolyte, an organic weak acid, an additive and the doped positive electrode material to a solvent to obtain a mixed slurry, and performing acid washing and coating on the doped positive electrode material in the mixed slurry to obtain an acid washed and coated material; the additive is one or more of borates and / or phosphates;

[0015] (3) calcining the acid-washed coated material to obtain a modified positive electrode material.

[0016] The second aspect of the present invention provides a modified positive electrode material prepared by the method described in the first aspect of the present invention.

[0017] Through the above technical solution, the beneficial technical effects achieved by the present invention are as follows:

[0018] 1) The preparation method of the modified positive electrode material provided in the present invention, the dopant, solid electrolyte, organic weak acid and additive work synergistically, and the total alkali content on the surface of the modified positive electrode material can be maintained in the range of 3000-8000ppm, which greatly improves the lithium ion migration rate of the positive electrode material, thereby effectively improving the first cycle efficiency, discharge capacity, rate performance, cycle performance and safety performance of the battery;

[0019] 2) The preparation method of the modified positive electrode material provided in the present invention preferably first uses a mild organic weak acid to react with the solid electrolyte material to form an acidic slurry, which can remove the intrinsic residual alkali on the surface of the solid electrolyte material and the positive electrode material and avoid destroying the surface structure of the material and introducing too many impurity elements, thereby further improving the lithium ion conductivity of the solid electrolyte material; after the additive is subsequently added, the doped positive electrode material is pickled and coated with the acidic slurry, and the over-washing phenomenon can be prevented by controlling the operating conditions during the pickling and coating process, thereby solving the gas generation problem of the positive electrode material during the cycle process, and improving the safety performance of the battery by improving the surface structure stability of the positive electrode material;

[0020] 3) The preparation method of the modified positive electrode material provided in the present invention can achieve uniform coating of the solid electrolyte by introducing additives, reduce interfacial side reactions, increase the lithium ion migration rate at the interface of the positive electrode material, and reduce the interfacial charge transfer impedance, thereby accelerating the electrode process kinetics and improving the rate performance and capacity performance;

[0021] 4) The preparation method of the modified positive electrode material provided in the present invention integrates the pickling process and the coating process into one, simplifies the process flow, and can improve the production efficiency and quality;

[0022] 5) The modified positive electrode material provided in the present invention has a large lithium ion diffusion coefficient, a total surface alkali content between 3000-8000ppm, a reasonable total surface alkali content, and excellent electrochemical properties, which can significantly improve the electrical properties and safety performance of lithium ion batteries. In addition, the preparation method is simple, the production efficiency is high, and it is suitable for industrial promotion. DETAILED DESCRIPTION

[0023] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0024] A first aspect of the present invention provides a method for preparing a modified positive electrode material, wherein the method comprises the following steps:

[0025] (1) mixing a positive electrode material and a dopant and calcining the mixture to obtain a doped positive electrode material; wherein the dopant is E m O n , 1≤m≤2, 1≤n≤5; E is selected from one or more of Zr, Y, Mg, Ti, Ca, Ce, La, Al, Nb, Ta, W, Mo, Sn, Sb, Sr;

[0026] (2) adding a solid electrolyte, an organic weak acid, an additive and the doped positive electrode material to a solvent to obtain a mixed slurry, and performing acid washing and coating on the doped positive electrode material in the mixed slurry to obtain an acid washed and coated material; the additive is one or more of borates and / or phosphates;

[0027] (3) calcining the acid-washed coated material to obtain a modified positive electrode material.

[0028] Among them, in the present invention, the inventors have found through research that in the process of modifying the positive electrode material, the synergistic effect of the dopant, solid electrolyte, organic weak acid and additive can effectively eliminate the damage caused to the positive electrode material by pickling and coating, and can minimize the introduction of impurities, ensure that the surface structure of the positive electrode material is not destroyed, and maintain the stability of the lattice structure of the positive electrode material, thereby significantly improving the lithium ion diffusion coefficient of the modified positive electrode material, greatly reducing the content of total alkali on the surface of the modified positive electrode material, and controlling the content of total alkali on the surface of the positive electrode material to between 3000-8000ppm, which helps to limit and improve the safety performance and electrochemical performance (especially the first week efficiency, discharge capacity, rate performance and cycle performance) of lithium-ion batteries.

[0029] In step (1):

[0030] In a preferred embodiment of the present invention, the positive electrode material is selected from a nickel-rich positive electrode material and / or a lithium-rich manganese-based positive electrode material. The present invention does not specifically limit the nickel-rich positive electrode material and the lithium-rich manganese-based positive electrode material, and the nickel-rich positive electrode material and the lithium-rich manganese-based positive electrode material modified or unmodified according to a known method in the art can be used in the present invention.

[0031] In a preferred embodiment of the present invention, the structural formula of the nickel-rich positive electrode material is LiNi x Co y Mn 1-x-y-m , Al m , O2, where 0.4≤x≤1, 0≤y≤0.4, 0≤m , ≤0.2; Further preferably, the structural formula of the nickel-rich positive electrode material is LiNi 0.9 Co 0.05 Mn 0.05 O2、LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.9 Co 0.1 O2、LiNi 0.8 Co 0.05 Al 0.15 One or more of O2.

[0032] Preferably, the structural formula of the lithium-rich manganese-based positive electrode material is x , Li2MnO3·(1-x , )LiTMO2, where 0 <x , <1, TM is selected from one or more of Ni, Co, Mn, Fe, Cr; further preferably, the structural formula of the lithium-rich manganese-based positive electrode material is Li 1.2 Ni 0.2 Mn 0.6 O2.

[0033] In a preferred embodiment of the present invention, the positive electrode material is selected from LiNi 0.9 Co 0.05 Mn 0.05 O2、LiNi 0.9 Co 0.1 O2、LiNi 0.8 Co 0.05 Al 0.15 O2、LiNi 0.5 Co 0.2 Mn 0.3 O2、Li1.2 Ni 0.2 Mn 0.6 One or more of O2.

[0034] In a preferred embodiment of the present invention, the dopant is selected from one or more of ZrO2, Y2O3, MgO, TiO2, CaO, CeO2, La2O3, Al2O3, Nb2O5, Ta2O5, WO3, MoO2, SnO2, Sb2O3, and SrO, and is preferably selected from one or more of WO3, Nb2O5, MoO2, and Ta2O5.

[0035] Among them, in the present invention, a specific metal oxide is used as a dopant, and the dopant has better compatibility with acid washing and coating, which can further improve the lithium ion diffusion coefficient of the modified positive electrode material.

[0036] In a preferred embodiment of the present invention, the particle size of the positive electrode material is larger than that of the dopant; wherein the particle size of the positive electrode material is 0.2-25 μm, preferably 3-12 μm; and the particle size of the dopant is 2-600 nm, preferably 30-200 nm.

[0037] Among them, in the present invention, by controlling the relative sizes of the positive electrode material and the dopant particle size, the surface structure of the positive electrode material can be further stabilized.

[0038] In a preferred embodiment of the present invention, the mass of the dopant is 0.01-5%, preferably 0.1-1%, of the mass of the positive electrode material.

[0039] Among them, in the present invention, too much dopant will reduce the capacity of the positive electrode material, which is not conducive to improving the electrical performance of the battery; too little dopant will not be conducive to stabilizing the surface structure of the positive electrode material and improving the safety performance of the battery.

[0040] In a preferred embodiment of the present invention, the positive electrode material and the dopant are mixed by a dry method.

[0041] In a preferred embodiment of the present invention, the calcination operating conditions include: a heating rate of 1-10°C / min, preferably 2-5°C / min; a calcination temperature of 200-900°C, preferably 500-800°C; and a calcination time of 5-20h, preferably 8-15h.

[0042] In a preferred embodiment of the present invention, the calcination operation conditions further include: the calcination is carried out in an atmosphere containing oxygen, for example, in air and / or oxygen, preferably in an oxygen atmosphere.

[0043] In step (2):

[0044] In a preferred embodiment of the present invention, the solid electrolyte is selected from one or more of NASICON-type oxide solid electrolytes, perovskite-type oxide solid electrolytes, and garnet-type oxide solid electrolytes.

[0045] In a preferred embodiment of the present invention, the molecular formula of the NASICON compound is Li 1+a A a B 2-a (PO4)3, wherein A is selected from one or more of Al, Fe, Cr, In, and Y; B is selected from one or more of Ti, Ge, Zr, Hf, and Sn, and 0≤a≤0.5; for example, Li 1.3 Al 0.3 Ti 1.7 (PO4)3、Li 1.4 Al 0.4 Ti 1.6 (PO4)3、Li 1.5 Al 0.5 Ti 1.5 (PO4)3、Li 1.5 Al 0.5 Ge 1.5 (PO4)3.

[0046] In a preferred embodiment of the present invention, the perovskite oxide solid electrolyte is Li 3b La 2 / 3-b TiO3, where 0<b≤2 / 3. For example, Li 0.33 La 0.56 TiO3.

[0047] In a preferred embodiment of the present invention, the garnet-type oxide solid electrolyte is Li 3+ z C3D2O 12 , wherein C is one or more of La, Ln, Y, and Nd, D is one or more of Ta, Nb, Bi, Sb, Zr, Hf, Sn, Te, and W, and 0≤z≤4; for example, Li7La3Zr2O 12 .

[0048] In a preferred embodiment of the present invention, the particle size of the solid electrolyte is 20-2000 nm, preferably 50-300 nm.

[0049] In a preferred embodiment of the present invention, the organic weak acid has a PKa of 3.5-10; further preferably, the organic weak acid is selected from one or more of oleic acid, formic acid, acetic acid, propionic acid, lactic acid, and stearic acid.

[0050] Among them, in the present invention, the inventors have found through research that the positive electrode material is contacted with an organic weak acid after being modified by a dopant, and the organic weak acid, solid electrolyte and additive interact with each other, which can solve the problem of residual inert metal oxides at the interface of the positive electrode material and improve the electrical performance of the battery. The synergistic effect of the dopant, organic weak acid, additive and solid electrolyte also helps to form a more stable CEI film, alleviate the surface particle pulverization phenomenon of the positive electrode material, improve the surface structural stability of the positive electrode material, and thus improve the safety performance of the battery.

[0051] In a preferred embodiment of the present invention, the additive is selected from one or more of lithium tetraborate, lithium phosphate, lithium dihydrogen phosphate, dilithium hydrogen phosphate, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, and ammonium phosphate.

[0052] Among them, in the present invention, the inventors have found through research that additives help to achieve uniform coating of solid electrolytes, thereby helping to improve the lithium ion diffusion coefficient of the modified positive electrode material.

[0053] In a preferred embodiment of the present invention, the particle size of the additive is 50-250 nm, preferably 100-200 nm.

[0054] In a preferred embodiment of the present invention, the solvent is selected from water and / or ethanol, preferably water.

[0055] In a preferred embodiment of the present invention, in the mixed slurry, the mass of the solid electrolyte is 0.01-15%, preferably 0.1-5%, of the mass of the doped positive electrode material.

[0056] Among them, in the present invention, the amount of solid electrolyte should not be too much relative to the doped positive electrode material, otherwise the initial capacity of the battery will be reduced, and the amount of solid electrolyte should not be too little relative to the doped positive electrode material, otherwise the surface lithium ion diffusion rate will be reduced. When the amount of solid electrolyte is within the above-defined range, the electrical properties of the modified positive electrode material are better.

[0057] In a preferred embodiment of the present invention, the mass of the additive is 0.01-5%, preferably 0.1-1%, of the mass of the doped positive electrode material.

[0058] In a preferred embodiment of the present invention, the amount of the organic weak acid added is such that the pH value of the mixed slurry is greater than or equal to 4 and less than 7, preferably greater than or equal to 4.5 and less than or equal to 6.5.

[0059] Among them, in the present invention, the pH should not be too low, otherwise it will destroy the surface structure of the positive electrode material. The pH should not be too high, otherwise it will not be conducive to reducing the content of total surface alkali. When the pH is within the above-defined range, the electrical properties of the modified positive electrode material are better.

[0060] In a preferred embodiment of the present invention, the operating conditions of the pickling and coating include: the pickling and coating temperature is 5-30°C, preferably 10-25°C; the pickling and coating time is 0.5-15min, preferably 1-5min; the stirring speed is 200-2000rpm, preferably 300-500rpm.

[0061] Among them, in the present invention, in the preparation method of the modified positive electrode material provided by the present invention, by controlling the operating conditions of the acid washing and coating, the total alkali content on the surface of the modified positive electrode material can be controlled within the range of 3000-8000ppm.

[0062] In a preferred embodiment of the present invention, the step (2) comprises: first dispersing the solid electrolyte and the additive into a solvent, and then adding an organic weak acid to obtain an acidic slurry; then adding the doped positive electrode material to the acidic slurry to obtain a mixed slurry, and acid-washing and coating the doped positive electrode material in the mixed slurry to obtain an acid-washed coated material.

[0063] Among them, in the present invention, the inventors have found through research that compared with adding solid electrolyte, organic weak acid, additives and doped positive electrode materials at the same time, first treating the solid electrolyte with organic weak acid and then adding additives and doped positive electrode materials for acid washing and coating is more conducive to improving the first week efficiency, discharge capacity, cycle performance and safety performance of the battery.

[0064] In a preferred embodiment of the present invention, after the acid washing and coating, solid-liquid separation, drying and sieving are performed to obtain the acid washing and coating material. The solid-liquid separation is preferably filtration, the drying temperature is 80-150°C, preferably 100-120°C; the sieving is preferably 400-600 mesh sieve.

[0065] In step (3):

[0066] In a preferred embodiment of the present invention, the calcination operation conditions further include: the calcination is carried out in an atmosphere containing oxygen, for example, the calcination is carried out in an oxygen atmosphere and / or an air atmosphere, preferably in an oxygen atmosphere.

[0067] In a preferred embodiment of the present invention, the calcination operating conditions include: calcination heating rate of 1-10°C / min, preferably 2-5°C / min; calcination temperature of 200-700°C, preferably 300-500°C; calcination time of 5-20h, preferably 8-15h.

[0068] The second aspect of the present invention provides a modified positive electrode material prepared by the method described in the first aspect of the present invention.

[0069] In a preferred embodiment of the present invention, the lithium ion diffusion coefficient of the modified positive electrode material is 10 -13 -10 -7 cm 2 / s, preferably 10 -10 -10 -8 cm 2 / s.

[0070] In a preferred embodiment of the present invention, the total surface alkali content of the modified positive electrode material is 3000-8000 ppm, preferably 4000-6000 ppm.

[0071] Among them, the modified positive electrode material prepared by the method of the present invention has a large lithium ion diffusion coefficient and a low content of total surface alkali, which can significantly improve the rate performance, cycle performance and safety performance of lithium ion batteries.

[0072] The present invention will be described in detail below through examples.

[0073] Example 1

[0074] (1) LiNi, a positive electrode material with a particle size of 10 μm 0.9 Co 0.05 Mn 0.05 O2 and WO3 with a particle size of 30nm were mixed evenly by dry method and then put into a muffle furnace for calcination. Under oxygen atmosphere, the temperature was raised to 700℃ at a heating rate of 5℃ / min and calcined at 700℃ for 10h to obtain a doped positive electrode material; wherein the mass of WO3 is LiNi 0.9 Co 0.05 Mn 0.05 0.2% of O2 mass;

[0075] (2) First, a solid electrolyte Li with a particle size of 120 nm was prepared. 1.3 Al 0.3 Ti 1.7(PO4)3 and lithium dihydrogen phosphate as an additive with a particle size of 150 nm are added to pure water, and after being uniformly dispersed under ultrasonic action, acetic acid (PKa=4.76) is added to adjust the pH to obtain an acidic slurry with a pH of 5; then the above-mentioned doped positive electrode material is added to the acidic slurry to obtain a mixed slurry, and the mixed slurry is acid-washed and coated, and then dried at 110°C and passed through a 400-mesh sieve to obtain an acid-washed and coated material;

[0076] Among them, the solid electrolyte Li 1.3 Al 0.3 Ti 1.7 The mass of (PO4)3 is 0.5% of the mass of the doped positive electrode material, the mass of the additive lithium dihydrogen phosphate is 0.1% of the mass of the doped positive electrode material, the temperature of the pickling and coating is 15°C, the stirring speed is 300rpm, and the time of the pickling and coating is 2min;

[0077] (3) The acid-washed coated material was heated to 300° C. at a heating rate of 2° C. / min in an oxygen atmosphere, and calcined at 300° C. for 10 h to obtain a modified positive electrode material.

[0078] Example 2

[0079] The same as Example 1, except that the pH of the mixed slurry is 4.

[0080] Example 3

[0081] The same as Example 1, except that the pH of the mixed slurry is 6.5.

[0082] Example 4

[0083] Same as Example 1, except that the solid electrolyte Li 1.3 Al 0.3 Ti 1.7 The particle size of (PO4)3 is 30nm.

[0084] Example 5

[0085] Same as Example 1, except that the solid electrolyte Li 1.3 Al 0.3 Ti 1.7 The particle size of (PO4)3 is 1200nm.

[0086] Example 6

[0087] Same as Example 1, except that the solid electrolyte Li 1.3 Al 0.3 Ti 1.7 The mass of (PO4)3 is 0.1% of the mass of the doped positive electrode material.

[0088] Example 7

[0089] Same as Example 1, except that the solid electrolyte Li 1.3 Al 0.3 Ti 1.7 The mass of (PO4)3 is 5% of the mass of the doped positive electrode material.

[0090] Example 8

[0091] The same as Example 1, except that the pickling and coating time is 1 min.

[0092] Example 9

[0093] The same as Example 1, except that the pickling and coating time is 15 minutes.

[0094] Example 10

[0095] Same as Example 1, except that the mass of WO3 is LiNi 0.9 Co 0.05 Mn 0.05 0.05% of the mass of O2.

[0096] Embodiment 11

[0097] Same as Example 1, except that the mass of WO3 is LiNi 0.9 Co 0.05 Mn 0.05 2% of the mass of O2.

[0098] Example 12

[0099] The same as Example 1, except that the particle size of WO3 is 500nm.

[0100] Example 13

[0101] (1) LiNi, a positive electrode material with a particle size of 15 μm 0.9 Co 0.1 O2 and dopant Nb2O5 with a particle size of 50nm were mixed evenly by dry method and then placed in a muffle furnace for calcination. In an oxygen atmosphere, the temperature was raised to 500℃ at a heating rate of 7℃ / min and calcined at 500℃ for 7h to obtain a doped positive electrode material; wherein the mass of Nb2O5 is LiNi 0.9 Co 0.1 2.2% of O2 mass;

[0102] (2) First, a solid electrolyte Li with a particle size of 50 nm was prepared. 0.33 La 0.56TiO3 and lithium tetraborate as an additive with a particle size of 50 nm are added to pure water, and after being uniformly dispersed under ultrasonic action, formic acid (PKa=3.75) is added to adjust the pH to obtain an acidic slurry with a pH of 4; then the above-mentioned doped positive electrode material is added to the acidic slurry to obtain a mixed slurry, and the mixed slurry is acid-washed and coated, and then dried at 110° C. and passed through a 400-mesh sieve to obtain an acid-washed and coated material;

[0103] Among them, the solid electrolyte Li 0.33 La 0.56 The mass of TiO3 is 0.2% of the mass of the doped positive electrode material, the mass of the additive lithium tetraborate is 0.5% of the mass of the doped positive electrode material, the temperature of the pickling and coating is 10°C, the stirring speed is 500rpm, and the time of the pickling and coating is 10min;

[0104] (3) The acid-washed coated material was heated to 200° C. at a heating rate of 2° C. / min in an oxygen atmosphere, and calcined at 200° C. for 10 h to obtain a modified positive electrode material.

[0105] Embodiment 14

[0106] (1) LiNi, a positive electrode material with a particle size of 2 μm 0.8 Co 0.05 Al 0.15 O2 and the dopant MoO2 with a particle size of 600nm were mixed evenly by dry method and then placed in a muffle furnace for calcination. In an oxygen atmosphere, the temperature was raised to 300℃ at a heating rate of 8℃ / min and calcined at 300℃ for 6h to obtain a doped positive electrode material; wherein the mass of MoO2 is LiNi 0.8 Co 0.05 Al 0.15 3.5% of O2 mass;

[0107] (2) First, solid electrolyte Li7La3Zr2O with a particle size of 500nm 12 and an additive lithium dihydrogen phosphate with a particle size of 200 nm are added to pure water, and after being evenly dispersed under ultrasonic action, propionic acid (PKa=4.87) is added to adjust the pH to obtain an acidic slurry with a pH of 6; then the above-mentioned doped positive electrode material is added to the acidic slurry to obtain a mixed slurry, and the mixed slurry is acid-washed and coated, and then dried at 110° C. and passed through a 400-mesh sieve to obtain an acid-washed and coated material;

[0108] Among them, the solid electrolyte Li7La3Zr2O 12 The mass of the doped positive electrode material is 8% of the mass of the doped positive electrode material, the mass of the additive lithium dihydrogen phosphate is 1.0% of the mass of the doped positive electrode material, the temperature of the pickling and coating is 12°C, the stirring speed is 1000rpm, and the time of the pickling and coating is 12min;

[0109] (3) The acid-washed coated material was heated to 380° C. at a heating rate of 2° C. / min in an oxygen atmosphere, and calcined at 380° C. for 10 h to obtain a modified positive electrode material.

[0110] Embodiment 15

[0111] (1) LiNi, a positive electrode material with a particle size of 10 μm 0.5 Co 0.2 Mn 0.3 O2 and dopant Ta2O5 with a particle size of 120nm were mixed evenly by dry method and then placed in a muffle furnace for calcination. In an oxygen atmosphere, the temperature was raised to 900℃ at a heating rate of 8℃ / min and calcined at 900℃ for 4h to obtain a doped positive electrode material; wherein the mass of Ta2O5 is LiNi 0.5 Co 0.2 Mn 0.3 4.5% of O2 mass;

[0112] (2) First, a solid electrolyte Li with a particle size of 1000 nm was 1.3 Al 0.3 Ti 1.7 (PO4)3 and lithium dihydrogen phosphate as an additive with a particle size of 250nm are added to pure water, and after being evenly dispersed under ultrasonic action, propionic acid (PKa=4.87) is added to adjust the pH to obtain an acidic slurry with a pH=4; then the above-mentioned doped positive electrode material is added to the acidic slurry to obtain a mixed slurry, and the mixed slurry is acid-washed and coated, and then dried at 110°C and passed through a 400-mesh sieve to obtain an acid-washed and coated material;

[0113] Among them, the mixed solid electrolyte Li 1.3 Al 0.3 Ti 1.7 The mass of (PO4)3 is 12% of the mass of the doped positive electrode material, the mass of the additive lithium dihydrogen phosphate is 2.0% of the mass of the doped positive electrode material, the temperature of the pickling and coating is 11°C, the stirring speed is 1000rpm, and the time of the pickling and coating is 11min;

[0114] (3) The acid-washed coated material was heated to 500° C. at a heating rate of 5° C. / min in an oxygen atmosphere, and calcined at 500° C. for 10 h to obtain a modified positive electrode material.

[0115] Example 16

[0116] (1) The positive electrode material Li with a particle size of 3 μm 1.2 Ni 0.2 Mn 0.6O2 and the dopant Nb2O5 with a particle size of 90nm were mixed evenly by dry method and then put into a muffle furnace for calcination. In an oxygen atmosphere, the temperature was raised to 450℃ at a heating rate of 1℃ / min and calcined at 450℃ for 16h to obtain a doped positive electrode material; wherein the mass of Nb2O5 is Li 1.2 Ni 0.2 Mn 0.6 0.01% of O2 mass;

[0117] (2) First, a solid electrolyte Li with a particle size of 1500 nm was 1.5 Al 0.5 Ti 1.5 (PO4)3 and an additive lithium phosphate with a particle size of 80 nm are added to pure water, and after being evenly dispersed under ultrasonic action, lactic acid (PKa=3.86) is added to adjust the pH to obtain an acidic slurry with a pH of 6; then the above-mentioned doped positive electrode material is added to the acidic slurry to obtain a mixed slurry, and the mixed slurry is acid-washed and coated, and then dried at 110°C and passed through a 400-mesh sieve to obtain an acid-washed and coated material;

[0118] Among them, the solid electrolyte Li 1.5 Al 0.5 Ti 1.5 The mass of (PO4)3 is 5% of the mass of the doped positive electrode material, the additive lithium phosphate is 2.5% of the mass of the doped positive electrode material, the temperature of the pickling and coating is 10°C, the stirring speed is 1500rpm, and the time of the pickling and coating is 3min;

[0119] (3) The acid-washed coated material was heated to 450° C. at a heating rate of 2° C. / min in an oxygen atmosphere, and calcined at 450° C. for 10 h to obtain a modified positive electrode material.

[0120] Embodiment 17

[0121] (1) LiNi, a positive electrode material with a particle size of 10 μm 0.9 Co 0.05 Mn 0.05 O2 and WO3 with a particle size of 30nm were mixed evenly by dry method and then put into a muffle furnace for calcination. Under oxygen atmosphere, the temperature was raised to 700℃ at a heating rate of 5℃ / min and calcined at 700℃ for 10h to obtain a doped positive electrode material; wherein the mass of WO3 is LiNi 0.9 Co 0.05 Mn 0.05 0.2% of O2 mass;

[0122] (2) First, a solid electrolyte Li with a particle size of 120 nm was prepared. 1.3 Al 0.3 Ti 1.7(PO4)3, acetic acid (PKa = 4.76) The additive lithium dihydrogen phosphate with a particle size of 150nm and the above-mentioned doped positive electrode material are added to the solvent, and the amount of acetic acid added is the same as that in Example 1, and the pH value is adjusted to obtain a mixed slurry of 5; the mixed slurry is acid-washed and coated, and then dried at 110°C and passed through a 400-mesh sieve to obtain an acid-washed and coated material;

[0123] Among them, the solid electrolyte Li 1.3 Al 0.3 Ti 1.7 The mass of (PO4)3 is 0.5% of the mass of the doped positive electrode material, the mass of the additive lithium dihydrogen phosphate is 0.1% of the mass of the doped positive electrode material, the temperature of the pickling and coating is 15°C, the stirring speed is 300rpm, and the time of the pickling and coating is 2min;

[0124] (3) The acid-washed coated material was heated to 300° C. at a heating rate of 2° C. / min in an oxygen atmosphere, and calcined at 300° C. for 10 h to obtain a modified positive electrode material.

[0125] Comparative Example 1

[0126] Compared with Example 1, the difference is that acetic acid is replaced by hydrochloric acid to obtain an acidic slurry with a pH of 3. The prepared modified positive electrode material is recorded as a comparative modified positive electrode material.

[0127] Comparative Example 2

[0128] Compared with Example 1, the difference is that in step (2), the solid electrolyte Li is omitted 1.3 Al 0.3 Ti 1.7 (PO4)3. The prepared modified positive electrode material is recorded as a comparative modified positive electrode material.

[0129] Comparative Example 3

[0130] Compared with Example 1, the difference is that in step (2), acetic acid is omitted. The prepared modified positive electrode material is recorded as a comparative modified positive electrode material.

[0131] Comparative Example 4

[0132] Compared with Example 1, the difference is that in step (1), the dopant WO3 is omitted. The prepared modified positive electrode material is recorded as a comparative modified positive electrode material.

[0133] Comparative Example 5

[0134] Compared with Example 1, the difference is that in step (2), the additive lithium dihydrogen phosphate is omitted. The prepared modified positive electrode material is recorded as a comparative modified positive electrode material.

[0135] Comparative Example 6

[0136] Without modification, the positive electrode material LiNi with a particle size of 10μm 0.9 Co 0.05 Mn 0.05 O2 is the comparative positive electrode material in Comparative Example 6.

[0137] Test Example 1

[0138] The modified positive electrode materials in Examples 1-17 and the comparative modified positive electrode materials and comparative positive electrode materials in Comparative Examples 1-6 were respectively prepared into button batteries, and then the lithium ion diffusion coefficient was tested. The preparation method of the button battery and the specific test method of the lithium ion diffusion coefficient are as follows:

[0139] The button battery preparation method is as follows: a positive electrode material, a binder PVDF and a conductive agent superP are mixed in a mass ratio of 95:2.5:2.5 and then added to NMP to obtain a positive electrode slurry with a theoretical solid content of 55wt%; the positive electrode slurry is coated on the positive electrode sheet with a coating thickness of 200μm, and a positive electrode sheet is obtained after drying; the positive electrode sheet, the negative electrode sheet (metal lithium sheet), the separator (Celgard 2400 single-layer microporous PP membrane) and the electrolyte (1 mol / L LiPF6 is dissolved in a mixed solution of EC / DMC / EMC with a volume ratio of 1:1:1) are assembled into a button half-cell in a high-purity argon glove box with strictly controlled water and oxygen content to obtain a button battery.

[0140] Then the battery is clamped in the battery fixture and connected to the blue electric test equipment to test the open circuit voltage, and then the process step editing software is opened on the blue electric test equipment to set the test program and fit the obtained data to the lithium ion diffusion coefficient under different SOC states. The fitting results of the lithium ion diffusion coefficient (50% SOC) are shown in Table 1.

[0141] Nickel-rich cathode material testing procedure:

[0142] Test equipment: Blue Electric Test Cabinet, test charge cut-off voltage 4.25V. Safety voltage 5V, nominal specific capacity 200mAh / g, first effect = discharge specific capacity / charge specific capacity*100%.

[0143] 1. 25℃, let stand for 4h;

[0144] 2. Constant current charging: If the 0.1C constant current charging time is ≥10min, jump to step 3;

[0145] 3. Standing: If the standing time is ≥ 1h, jump to step 4;

[0146] 4. Constant current charging: If the 0.1C constant current charging time is ≥10min, jump to step 5;

[0147] 5. If the voltage is less than 4.25V, jump to step 3; if the voltage is greater than or equal to 4.25V, jump to step 6;

[0148] 6. Constant current discharge: If the 0.1C constant current discharge time is ≥10min, jump to step 7;

[0149] 7. Standing: If the standing time is ≥ 1h, jump to step 8;

[0150] 8. Constant current discharge: If the 0.1C constant current discharge time is ≥10min, jump to step 9;

[0151] 9. If the voltage is greater than 2.5V, go to step 7. If the voltage is less than or equal to 2.5V, the test ends.

[0152] Lithium-rich manganese-based cathode material testing procedures:

[0153] Test equipment: Blue Electric Test Cabinet, test charge cut-off voltage 4.8V. Safety voltage 5V, nominal specific capacity 300mAh / g, first effect = discharge specific capacity / charge specific capacity*100%.

[0154] 1. 25℃, let stand for 4h;

[0155] 2. Constant current charging: If the 0.1C constant current charging time is ≥10min, jump to step 3;

[0156] 3. Standing: If the standing time is ≥ 1h, jump to step 4;

[0157] 4. Constant current charging: If the 0.1C constant current charging time is ≥10min, jump to step 5;

[0158] 5. If the voltage is less than 4.8V, jump to step 3; if the voltage is ≥4.8V, jump to step 6; 6. Constant current discharge: if the 0.1C constant current discharge time is ≥10min, jump to step 7;

[0159] 7. Standing: If the standing time is ≥ 1h, jump to step 8;

[0160] 8. Constant current discharge: If the 0.1C constant current discharge time is ≥10min, jump to step 9;

[0161] 9. If the voltage is greater than 2.5V, go to step 7. If the voltage is less than or equal to 2.5V, the test ends.

[0162] Table 1

[0163]

[0164]

[0165] Test Example 2

[0166] The total surface alkali content of the modified positive electrode materials in Examples 1-17 and the comparative modified positive electrode materials and comparative positive electrode materials prepared in Comparative Examples 1-6 was tested. The test results are shown in Table 2.

[0167] Among them, the specific test method for the total surface alkali content is as follows:

[0168] 1. Take 30.0000g sample, accurate to 0.0001g, place it in a 200mL blue-cap bottle, add 100mL ultrapure water, stir magnetically for 30min, speed 600r / min, let it stand for 5min, then filter and collect the filtrate; use a pipette to transfer 50mL of filtrate to a beaker for testing.

[0169] 2. Test: Turn on the fully automatic potentiometric titrator (Swiss Metrohm 916Ti-touch) and prepare for titration. Remove the bubbles in the pipeline, clean the titration head and stirring paddle with ultrapure water, and use dust-free paper to absorb excess water, and prepare for the test;

[0170] Enter the acid-base titration method, insert the electrode, titration head and stirrer into the filtrate after pretreatment, make the electrode bulb below the liquid surface, click Start, enter the sample mass (1 / 2 of the sample weight) as prompted, and record the equivalence point volumes V1 and V2.

[0171] 3. Result processing:

[0172] LiOH(ppm)=c*(2V1-V2)*23.95*1000 / m

[0173] Li2CO3(ppm)=c*(V2-V1)*73.89*1000 / m

[0174] Total surface alkali (ppm) = LiOH (ppm) / 23.948 * 73.891 / 2 + Li2CO3 (ppm).

[0175] Where c is the concentration of dilute hydrochloric acid, the titrant, in mol / L;

[0176] m is the mass of the sample (1 / 2 of the sample weight), in g; V1 and V2 are the equivalence point volumes, in / mL.

[0177] Table 2

[0178]

[0179]

[0180] It can be seen from the results in Table 1-2 that the modified positive electrode materials prepared in Examples 1-17 of the present invention can significantly improve the lithium ion diffusion coefficient of the positive electrode material and significantly reduce the total surface alkali content of the positive electrode material.

[0181] (1) Effect of acid type and pH on the performance of modified cathode materials

[0182] It can be seen from Table 1 and Table 2 that the total surface alkali of Examples 1-3 and Comparative Example 1 is 4728 ppm, 3546 ppm, 7156 ppm and 2986 ppm respectively; the lithium ion diffusion coefficient is 2.56*10 -8 cm 2 / s, 2.48*10 -9 cm 2 / s, 5.92*10 -9 cm 2 / s and 1.24*10 -10 cm 2 / s.

[0183] By comparing the data of Examples 1-3, it can be seen that the modified positive electrode material obtained by the preparation method of the present invention, as the pH of the slurry decreases, the total alkali content on the surface of the modified positive electrode material also decreases. By comparing Examples 1-3 and Comparative Example 1, it can be seen that the type of acid and pH have a significant effect on the performance of the modified positive electrode material. Among them, although the use of hydrochloric acid and a pH that is too low can further reduce the total alkali content on the surface of the modified positive electrode material, it is also easy to produce overwashing, which destroys the surface structure of the modified positive electrode material, thereby causing the lithium ion diffusion coefficient of the positive electrode material to decrease. Therefore, when an organic weak acid is used and the pH is within the range defined by the present invention, the total alkali content on the surface of the modified positive electrode material can be reduced and controlled between 3000-8000ppm, without overwashing to destroy the structure and affect the lithium ion diffusion coefficient.

[0184] (2) Effect of pickling time on the performance of modified cathode materials

[0185] The total surface alkali of Example 1 and Examples 8-9 are 4728ppm, 5896ppm and 3472ppm respectively; the lithium ion diffusion coefficients are 2.56*10 -8 cm 2 / s, 4.78*10 -9 cm 2 / s and 2.36*10 -9 cm 2 / s. It can be seen from this that when the pickling time is within the range specified in the present invention, the modified positive electrode material can have both reasonable surface total alkali and lithium ion diffusion coefficient.

[0186] (3) Effect of solid electrolyte particle size and dosage on the performance of modified positive electrode materials

[0187] By comparing the data of Example 1 and Examples 4-5, it can be seen that the total surface alkali contents of Examples 1 and Examples 4-5 are 4728 ppm, 5342 ppm and 5542 ppm respectively; the lithium ion diffusion coefficients are 2.56*10 -8 cm 2 / s, 4.02*10 -9 cm 2 / s and 3.87*10 -9 cm 2 / s, it can be seen that the solid electrolyte particle size is within the range specified by the present invention, which can ensure that the particle size will not be too small to cause agglomeration during the preparation process and will not affect the trial production process due to excessive particle size, thereby ensuring the lithium ion diffusion coefficient of the positive electrode material.

[0188] The total surface alkali contents of Examples 6 and 7 were 4656 ppm and 4986 ppm respectively; the lithium ion diffusion coefficients were 8.96*10 -9 cm 2 / s, 4.21*10 -9 cm 2 / s, it can be seen that the solid electrolyte content is within the range specified in the present invention, which can ensure that the content is not too low to cause the coating layer to be too thin or uneven, and the content is not too high to cause the coating layer to be too thick, thereby ensuring the lithium ion diffusion performance of the positive electrode material.

[0189] (4) Effect of dopant particle size and dosage on the performance of modified positive electrode materials

[0190] By comparing the data of Example 1 and Examples 10-12, it can be seen that the total surface alkali of Example 1 and Examples 10-12 are 4728ppm, 4756ppm, 4641ppm and 4852ppm respectively; the lithium ion diffusion coefficients are 2.56*10 -8 cm 2 / s, 6.32*10 - 9 cm 2 / s, 7.85*10 -9 cm 2 / s and 5.78*10 -9 cm 2 / s, it can be seen that when the particle size and amount of the dopant are within the range defined by the present invention, it is more conducive to increasing the lithium ion diffusion coefficient of the modified positive electrode material. This may be because when the particle size and amount of the dopant are within the range defined by the present invention, the doping agent can be better doped into the surface of the positive electrode material, further improving the bond energy between the doping element and the oxygen atoms on the positive electrode material, which is more conducive to stabilizing the surface structure of the modified positive electrode material without excessively affecting the lithium ion diffusion coefficient of the positive electrode material.

[0191] (5) The effect of the synergistic effect of dopants, solid electrolytes, organic weak acids and additives on the performance of modified cathode materials in the preparation method

[0192] By comparing the data of Example 1 and Comparative Examples 2-6, it can be seen that the total surface alkali of Example 1 and Comparative Examples 2-6 are 4728ppm, 4832ppm, 8509ppm, 5186ppm, 5201ppm and 9027ppm respectively; the lithium ion diffusion coefficients are 2.56*10 - 8 cm 2 / s, 9.21*10 -10 cm 2 / s, 1.12*10 -11 cm 2 / s, 8.27*10 -10 cm 2 / s, 8.14*10 -10 cm 2 / s and 9.23*10 - 12 cm 2 / s, it can be seen that the dopant, organic weak acid, additive and solid electrolyte work synergistically to reduce the total alkali content on the surface of the modified positive electrode material while improving the lithium ion diffusion coefficient of the modified positive electrode material.

[0193] Test Example 3

[0194] The modified positive electrode materials prepared in Examples 1-17 and the comparative modified positive electrode materials and comparative positive electrode materials prepared in Comparative Examples 1-6 were prepared into button batteries and then tested. The specific testing method is as follows:

[0195] The button battery preparation method is as follows: the positive electrode material, the binder PVDF and the conductive agent superP are mixed in a mass ratio of 95:2.5:2.5 and then added to NMP to obtain a positive electrode slurry with a theoretical solid content of 55wt%; the positive electrode slurry is coated on the positive electrode sheet with a coating thickness of 200um, and the positive electrode sheet is obtained after drying; the positive electrode sheet, the negative electrode sheet (metal lithium sheet), the separator (Celgard 2400 single-layer microporous PP membrane) and the electrolyte (1 mol / L LiPF6 is dissolved in a mixed solution of EC / DMC / EMC with a volume ratio of 1:1:1) are assembled into a button half-cell in a high-purity argon glove box with strictly controlled water and oxygen content to obtain a button battery.

[0196] Nickel-rich cathode material testing procedure:

[0197] Test equipment: Blue Electric Test Cabinet, test charge cut-off voltage 4.25V. Safety voltage 5V, nominal specific capacity 200mAh / g, first effect = discharge specific capacity / charge specific capacity*100%.

[0198] 1. 25℃, let stand for 4h;

[0199] 2. Charge at 0.1C constant current to 4.25V, charge at 4.25V constant voltage to the cut-off current ≤ 0.05C, and leave for 5 minutes;

[0200] 3. Discharge at 0.1C constant current until 2.5V, then stop.

[0201] Lithium-rich manganese-based cathode material testing procedures:

[0202] Test equipment: Blue Electric Test Cabinet, test charge cut-off voltage 4.8V. Safety voltage 5V, nominal specific capacity 300mAh / g, first effect = discharge specific capacity / charge specific capacity*100%.

[0203] 1. 25℃, let stand for 4h;

[0204] 2. Charge at 0.1C constant current to 4.8V, charge at 4.8V constant voltage to cut-off current ≤ 0.05C, and leave for 5 minutes; 3. Discharge at 0.1C constant current to 2.5V, then stop.

[0205] Table 3

[0206]

[0207]

[0208] It can be seen from the results in Table 3 that the battery assembled with the modified positive electrode material prepared in the embodiment of the present invention has significantly better effects in terms of first efficiency and discharge specific capacity performance.

[0209] (1) Effect of pH on battery performance

[0210] By comparing the data of Examples 1-3 and Comparative Example 1, it can be seen that the first efficiencies of Examples 1-3 and Comparative Example 1 are 92.12%, 88.92%, 90.65%, and 85.78%, respectively; the discharge specific capacities are 222.93mAh / g, 215.12mAh / g, 219.89mAh / g, and 205.59mAh / g, respectively. It can be seen that the first coulombic efficiency and discharge specific capacity of the modified positive electrode material obtained by the preparation method of the present invention are much higher than those of the untreated positive electrode material, and the first coulombic efficiency and discharge specific capacity of the modified positive electrode material prepared by acetic acid at a pH value greater than or equal to 4 and less than 7 are significantly higher than those of the modified positive electrode material prepared by a strong acid at a pH value less than 4. This is mainly because too low a pH value will lead to over-washing, thereby destroying the structure of the modified positive electrode material, resulting in a decrease in the first coulombic efficiency and discharge specific capacity of the battery; too high a pH value will not achieve the effect of reducing the total surface alkali, thereby affecting the first coulombic efficiency and discharge specific capacity of the battery.

[0211] (2) Effect of pickling time on battery performance

[0212] By comparing the data of Example 1 and Examples 8-9, it can be seen that the first efficiencies of Example 1 and Examples 8-9 are 92.12%, 90.12% and 88.75%, respectively; the discharge specific capacities are 222.93mAh / g, 218.28mAh / g and 213.54mAh / g, respectively. It can be seen that in the method provided by the present invention, the first coulombic efficiency and the discharge specific capacity can be further improved when the pickling time is within the range specified by the present invention.

[0213] (3) Effect of solid electrolyte particle size and dosage on battery performance

[0214] By comparing the data of Example 1 and Examples 4-7, it can be seen that the first efficiencies of Example 1 and Examples 4-7 are 92.12%, 89.54%, 89.12%, 91.11% and 89.98% respectively; the discharge specific capacities are 222.93mAh / g, 217.03mAh / g, 216.97mAh / g, 220.42mAh / g and 217.75mAh / g respectively. It can be seen that when the solid electrolyte particle size is within the range defined by the present invention, it is more conducive to improving the first coulombic efficiency of the battery and the discharge specific capacity of the battery; this may be because, when the solid electrolyte content is within the range defined by the present invention, it can ensure that the solid electrolyte content is not too low, resulting in a too thin or uneven coating layer, and the coating layer will not be too thick due to excessive content, and the coating thickness on the modified positive electrode material is more reasonable, thereby making the first coulombic efficiency of the battery and the discharge specific capacity of the battery higher.

[0215] (4) Effect of dopant particle size and dosage on battery performance

[0216] By comparing the data of Example 1 and Examples 10-12, it can be seen that the first efficiencies of Example 1 and Examples 10-12 are 92.12%, 90.72%, 90.91% and 90.54%, respectively; the discharge specific capacities are 222.93mAh / g, 220.15mAh / g, 220.21mAh / g and 219.02mAh / g, respectively. It can be seen that when the particle size and amount of the dopant are within the range specified by the present invention, it is helpful to further improve the first coulombic efficiency and discharge specific capacity of the battery.

[0217] (5) The influence of the synergistic effect of dopants, solid electrolytes, organic weak acids and additives in the preparation method on battery performance

[0218] By comparing the data of Example 1 and Comparative Examples 2-6, it can be seen that the first efficiency and discharge specific capacity of Example 1 and Comparative Examples 2-6 are 92.12%, 86.92%, 83.28%, 86.52%, 86.21% and 82.36% respectively; 222.93mAh / g, 208.61mAh / g, 203.48mAh / g, 208.23mAh / g, 208.15mAh / g and 201.21mAh / g. It can be seen that the dopant, organic weak acid, additive and solid electrolyte in the preparation method of the present invention act synergistically with each other, which can further improve the first coulombic efficiency and discharge specific capacity of the battery, thereby improving the electrochemical performance of the battery.

[0219] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a modified positive electrode material, characterized in that: The method comprises the following steps: (1) mixing a positive electrode material and a dopant and calcining the mixture to obtain a doped positive electrode material; wherein the dopant is E m O n , 1≤m≤2, 1≤n≤5; E is selected from one or more of Zr, Y, Mg, Ti, Ca, Ce, La, Al, Nb, Ta, W, Mo, Sn, Sb, Sr; (2) adding a solid electrolyte, an organic weak acid, an additive and the doped positive electrode material to a solvent to obtain a mixed slurry, and performing acid washing and coating on the doped positive electrode material in the mixed slurry to obtain an acid washed and coated material; the additive is one or more of borates and / or phosphates; (3) calcining the acid-washed coated material to obtain a modified positive electrode material.

2. The preparation method according to claim 1, characterized in that: The positive electrode material is selected from nickel-rich positive electrode materials and / or lithium-rich manganese-based positive electrode materials; Preferably, the structural formula of the nickel-rich positive electrode material is LiNi x Co y Mn 1-x-y-m , Al m , O2, where 0.4≤x≤1, 0≤y≤0.4, 0≤m , ≤0.2; Preferably, the structural formula of the lithium-rich manganese-based positive electrode material is x , Li2MnO3·(1-x , )LiTMO2, where 0 <x , <1, TM is selected from one or more of Ni, Co, Mn, Fe, Cr; Preferably, the dopant is selected from one or more of ZrO2, Y2O3, MgO, TiO2, CaO, CeO2, La2O3, Al2O3, Nb2O5, Ta2O5, WO3, MoO3, SnO2, Sb2O3, SrO; Preferably, the particle size of the positive electrode material is larger than the particle size of the dopant; Preferably, the particle size of the positive electrode material is 0.2-25 μm, preferably 3-12 μm; Preferably, the particle size of the dopant is 2-600 nm, preferably 30-200 nm; Preferably, the mass of the dopant is 0.01-5%, preferably 0.1-1%, of the mass of the positive electrode material.

3. The preparation method according to claim 1 or 2, characterized in that: The calcination operating conditions include: a heating rate of 1-10°C / min, preferably 2-5°C / min; a calcination temperature of 200-900°C, preferably 500-800°C; a calcination time of 5-20h, preferably 8-15h; and the calcination is carried out in an oxygen-containing atmosphere.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The solid electrolyte is selected from one or more of NASICON-type oxide solid electrolytes, perovskite-type oxide solid electrolytes, and garnet-type oxide solid electrolytes; Preferably, the NASICON type oxide solid electrolyte is Li 1+a A a B 2-a (PO4)3, wherein A is selected from one or more of Al, Fe, Cr, In, and Y; B is selected from one or more of Ti, Ge, Zr, Hf, and Sn, and 0≤a≤0.5; Preferably, the perovskite oxide solid electrolyte is Li 3b La 2 / 3-b TiO3, where 0<b≤2 / 3; Preferably, the garnet-type oxide solid electrolyte is Li 3+z C3D2O 12 , wherein C is selected from one or more of La, Ln, Y, and Nd, D is selected from one or more of Ta, Nb, Bi, Sb, Zr, Hf, Sn, Te, and W, and 0≤z≤4; Preferably, the particle size of the solid electrolyte is 20-2000 nm, preferably 50-300 nm.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The pKa of the organic weak acid is 3.5-10; Preferably, the organic weak acid is selected from one or more of oleic acid, formic acid, acetic acid, propionic acid, lactic acid and stearic acid.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The additive is selected from one or more of lithium tetraborate, lithium phosphate, lithium dihydrogen phosphate, dilithium hydrogen phosphate, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, and ammonium phosphate.

7. The preparation method according to any one of claims 1 to 6, characterized in that: In the mixed slurry, the mass of the solid electrolyte is 0.01-15% of the mass of the doped positive electrode material, preferably 0.1-5%; Preferably, the amount of the organic weak acid added is such that the pH value of the mixed slurry is greater than or equal to 4 and less than 7, preferably greater than or equal to 4.5 and less than or equal to 6.5; Preferably, the mass of the additive is 0.01-5%, preferably 0.1-1%, of the mass of the doped positive electrode material.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The operating conditions of the pickling and coating include: the pickling and coating temperature is 5-30°C, preferably 10-25°C; the pickling and coating time is 0.5-15min, preferably 1-5min; the stirring speed is 200-2000rpm, preferably 300-500rpm.

9. The preparation method according to any one of claims 1 to 8, characterized in that: First, the solid electrolyte and additives are dispersed in a solvent, and then an organic weak acid is added to obtain an acidic slurry; then, the doped positive electrode material is added to the acidic slurry to obtain a mixed slurry, and the doped positive electrode material is acid-washed and coated in the mixed slurry to obtain an acid-washed and coated material.

10. The preparation method according to any one of claims 1 to 9, characterized in that: The operating conditions of the calcination include: a calcination heating rate of 1-10°C / min, preferably 2-5°C / min; a calcination temperature of 200-700°C, preferably 300-500°C; a calcination time of 5-20h, preferably 8-15h; and the calcination is carried out in an oxygen-containing atmosphere.

11. A modified positive electrode material prepared by the preparation method according to any one of claims 1 to 10; Preferably, the lithium ion diffusion coefficient of the modified positive electrode material is 10 -13 -10 -7 cm 2 / s, preferably 10 -10 -10 -8 cm 2 / s; Preferably, the total surface alkali content of the modified positive electrode material is 3000-8000 ppm, preferably 4000-6000 ppm.

Citation Information

Patent Citations

  • Method for coating and modifying high-nickel ternary positive electrode material by one-step low-temperature water washing

    CN111682190A